1987
DOI: 10.1007/bf03259865
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Low-Level Lead Exposure

Abstract: Lead is a common element in the earth's crust, serving useful purposes in industry, but serving no purpose in the human body. Increase in blood pressure is an important public health problem with numerous factors contributing to many facets of the disease. The relationship of lead exposure and increased blood pressure has long been considered, but only recently critically investigated. Reports of subtle changes in calcium metabolism and renal function, as well as in vitro studies examining end-arteriolar smoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(14 citation statements)
references
References 143 publications
1
13
0
Order By: Relevance
“…Mazzali et al (2001a) reported that increased systolic blood pressure was correlated with serum uric acid. Increased systolic blood pressure was associated with lead dose in the same Korean lead worker population studied in this report (Lee et al 2001); similar associations have also been reported in other populations (Sharp et al 1987). Increased juxtaglomerular renin staining was present in the uric acid model (Mazzali et al 2001a).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Mazzali et al (2001a) reported that increased systolic blood pressure was correlated with serum uric acid. Increased systolic blood pressure was associated with lead dose in the same Korean lead worker population studied in this report (Lee et al 2001); similar associations have also been reported in other populations (Sharp et al 1987). Increased juxtaglomerular renin staining was present in the uric acid model (Mazzali et al 2001a).…”
Section: Discussionsupporting
confidence: 89%
“…Data suggest that lead exposure also increases renin; this effect may vary with length of exposure. Several reviews have concluded that renin is increased with short- to moderate-term lead exposure in both animals and humans but is normal or decreased with prolonged exposure (Gonick and Behari 2002; Sharp et al 1987; Vander 1988). Decreased neuronal nitric oxide synthase expression in the macula densa was reported in rodents in the uric acid model (Mazzali et al 2001a).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing body of evidence suggests that lead is associated with a number of health conditions that are also causes of cognitive decline, including hypertension (Hertz-Picciotto and Croft 1993; Hu et al 1996a; Nash et al 2003; Sharp et al 1987), elevated homocysteine levels (Schafer et al 2005), and psychiatric symptoms (Rhodes et al 2003; Schwartz et al 2001). Each of these health conditions may mediate or moderate (or confound, in the absence of temporality) relations between lead dose and cognitive function.…”
Section: Other Methodologic Considerationsmentioning
confidence: 99%
“…Several reviews and metaanalyses combining data from more than 30 original studies and around 60,000 participants have examined the evidence relating blood lead to blood pressure or hypertension [Hertz-Picciotto and Croft 1993; Nawrot et al 2002; Schwartz 1995; Sharp et al 1987; Staessen et al 1994, 1995; U.S. Environmental Protection Agency (U.S. EPA) 2006].…”
Section: Introductionmentioning
confidence: 99%